Lessons Learned While Migrating From Swing to JavaFX - Robillard, Martin P.; Kutschera, Kaylee (IEEE software, 2020)
We describe a case study of the migration of an interactive diagramming tool written in Java from the Swing graphical user interface framework to JavaFX. The outcome is presented as five lessons about the search for information when migrating software between major frameworks.